Fast-Fashion Laughing: Irreverence, Imitation and Innovation (ModaPalavra e-periódico, 2015)
In this paper we analyze strategies used by Budha Khe Rhi, a Brazilian fashion company. Our research approach was single case study, based on document analysis, field observation and interviews with company's marketing director. In order to analyze strategies the company has implemented to innovate, we adopted the Ten Types of Innovation Framework (KELLEY et al, 2013). Budha Khe Rhi has developed as a well-known brand associated with lifestyle and experiences that young people value. Nowadays, after expansion by means of opening new stores and franchising, the company is transitioning to a strategy near to fast-fashion. Results show that it stands out in seven of the ten types of innovation framework: Profit model and Network (Configuration); Product performance (Offering); and Service, Channel, Brand and Customer Engagement (Experience). Product is not its strong point, although they have some remarkable innovations. The major innovations involve a new way to interact with fans and share the brand lifestyle. The main factor that fosters innovation is related to managers' predisposition to encourage collaborators to think about best practices on their work and also implement new solutions.
Keywords: fast-fashion; fashion brand; types of innovation